THE ROLE OF INSTAGRAM SOCIAL MEDIA IN PROMOTING ROOM SALES AT HOTEL DA VIENNA BOUTIQUE BATAM - Selva, Jenny Miranda (SABA: Journal of Tourism Research, 2024)
The followers of Instagram caused the lack of interest of Instagram users in the promotion of room sales. This research is a descriptive qualitative research that aims to determine the role of Instagram social media in promoting room sales. The object of this research is the social media instagram @daviennaboutiquehotelbatam. Information in this study is the Sales and Marketing Department. To obtain data, researcher use several methods, namely primary data in the form of interviews, documentation and observation. For secondary data in the form of literature data, and books. There are two categories of informants for research as the object of research, hotel workers and external sources as additional informants.